Parallel generation of base relation snapshots for materialised view maintenance in data warehouse environment. (13th November 2007) - Saeki, Shin'ichirou; Bhalla, Subhash; Hasegawa, Masaki
A data warehouse organises and stores data needed for informational, analytical processing over a long historical time perspective. These keep a materialised view (such as historical data), and user queries are processed using this view. The view has to be maintained to reflect the updates done against the base relations stored at the various distributed data sources. For unsophisticated sources, in practice it is often necessary to infer modifications by periodically comparing snapshots and backup copies of data from the source. This study considers the materialised view and its maintenance. Various differential snapshot algorithms have been compared.